2005
DOI: 10.3998/ark.5550190.0006.931
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical study of arene carboxylic acids

Abstract: Dedicated to Professor AbstractWe analyze and compare the energetics of arenoic acids from studies of thermodynamic data such as the enthalpy of formation, ∆ f H°m. This quantity offers a powerful procedure for the understanding of the contrasting structural, conformational, and reactivity trends exhibited by compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 8 publications
4
12
0
Order By: Relevance
“…In our work, we showed that 3-thiophenecarboxylic acid is slightly more stable, thermodynamically, than 2-thiophenecarboxylic acid with an isomerization enthalpy of 2.6 kJ‚mol -1 . In the comparison with benzene and its analogous substituted benzene, benzoic acid, we showed that the 2-isomer is destabilized by 2.4 kJ‚mol -1 as a result of the through-space interaction between the oxygen of the hydroxyl group with the sulfur atom, 16 as opposed to stabilization because of an S‚‚‚H‚‚‚O hydrogen bond. With the result obtained with 3-thiophenecarboxylic acid, -0.2 kJ‚mol -1 , we concluded that there are not significant differences between the substituent effects produced by a carboxyl group in benzene and the 3-position in thiophene.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In our work, we showed that 3-thiophenecarboxylic acid is slightly more stable, thermodynamically, than 2-thiophenecarboxylic acid with an isomerization enthalpy of 2.6 kJ‚mol -1 . In the comparison with benzene and its analogous substituted benzene, benzoic acid, we showed that the 2-isomer is destabilized by 2.4 kJ‚mol -1 as a result of the through-space interaction between the oxygen of the hydroxyl group with the sulfur atom, 16 as opposed to stabilization because of an S‚‚‚H‚‚‚O hydrogen bond. With the result obtained with 3-thiophenecarboxylic acid, -0.2 kJ‚mol -1 , we concluded that there are not significant differences between the substituent effects produced by a carboxyl group in benzene and the 3-position in thiophene.…”
Section: Introductionmentioning
confidence: 93%
“…Over the past years, we have been involved in a thermochemical study of the energetic effects of sulfur compounds, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] among them thiophene derivatives. 6,9,16,17 The fundamental interest in this work is the understanding of structural effects on thermodynamic stabilities that are reflected on the enthalpies of formation for the compounds studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, we have been involved in a thermochemical study of the energetics of thiophene derivatives. A development of an understanding of the structural effects on thermodynamic stabilities reflected in the gas-phase enthalpies of formation of the compounds studied has been of fundamental interest to us. Substituents on the five-membered ring of thiophene have a different relationship to one another than similar substituents in benzene.…”
Section: Introductionmentioning
confidence: 99%